UrFear Huhu and The Multitude of Peer Gynts sebagai Tawaran Liveness pada Pertunjukan Virtual - Michael H.B. Raditya (Jurnal Kajian Seni, 2021)
This article deals with the “liveness” debate of virtual performance. Liveness is the most discussed issue when various artists choose virtual performances for their work. One of the reasons for the largest number of medium migration from live shows to virtual shows is the Covid-19 pandemic, that throughout 2020. In this article, the issue of liveness is linked to the liveness debate from scholar performance studies, Peggy Phelan, Philip Auslander, and Daniel Meyer-Dinkgräfe. Daniel Meyer-Dinkgräfe suggested that virtual performance have to be formulated differently from live performance. Regarding the suggestion, this article will discuss a virtual performance from Teater Garasi, “UrFear: Huhu and the Multitude Peer of Gynts”. Furthermore, this article investigates the various modes of performance in Teater Garasi performances. This investigation reveals the Moda initiative and special treatment that they did. According to the choice of performance modes and special treatments, Teater Garasi’s can offer the presence of liveness in virtual performance. Artikel ini membahas tentang tawaran liveness pada pertunjukan virtual. Liveness menjadi persoalan yang paling banyak dibicarakan ketika pelbagai seniman memilih pertunjukan virtual sebagai medium mereka berkarya. Salah satu penyebab banyaknya migrasi medium dari pertunjukan langsung ke pertunjukan virtual adalah pandemi Covid-19    yang terjadi sepanjang tahun 2020. Di dalam artikel ini, ihwal liveness akan ditautkan dengan perdebatan liveness dari scholar performance studies, Peggy Phelan, Philip Auslander, dan Daniel Meyer-Dinkgräfe. Khususnya Daniel Meyer-Dinkgräfe menyarankan agar pertunjukan virtual memiliki formulasi yang berbeda dari pertunjukan live. Atas dasar itu, artikel ini akan menautkan pertunjukan virtual Teater Garasi yang bertajuk UrFear: Huhu and the Multitude Peer of Gynts. Lebih lanjut, artikel ini menginvestigasi ragam moda performans pada pertunjukan Teater Garasi. Investigasi ini ditautkan dengan mempertanyakan liveness dan perlakuan khusus yang dilakukan Teater Garasi dalam menciptakan pertunjukannya. Bertolak dari pilihan moda performans dan perlakuan khusus yang ditawarkan, pertunjukan virtual Teater Garasi dapat menjadi tawaran akan hadirnya liveness pada pertunjukan virtual.